Evaluation and treatment of hip pain in the lacrosse athlete - Anthony J. Zacharias; Andrea M. Spiker (Elsevier, 2022)
Introduction: Lacrosse continues to be one of the fastest growing sports in the United States. Despite this, few studies look at evaluation and management of hip-related injuries, and one of the leading causes of hip injury, femoroacetabular impingement syndrome, in lacrosse athletes. Objectives: The purpose of this article is to review stepwise diagnosis and management of femoroacetabular impingement syndrome in the lacrosse athlete. This review takes into account the uniqueness of the sport as both a cutting and overhead sport. Methods: A review of recent literature and expert opinion was utilized in providing current diagnosis and management strategies for treating hip pain in the lacrosse athlete. Results: Limited research exists specific to outcomes in lacrosse athletes, however, previous studies have shown high return to sport rates. Conclusions: A stepwise approach to diagnosis and treatment of lacrosse athletes should be utilized with consideration given to the demands of the sport, both cutting and overhead. Prior to proceeding with hip arthroscopy, conservative treatments should be trialed, and even if surgery is required, can often be used to delay surgery until the off season.